PENGEMBANGAN BAHAN AJAR DILENGKAPI VIDEO PEMBELAJARAN DENGAN PENDEKATAN CTL PADA MATERI ORGAN TUBUH MANUSIA DAN HEWAN UNTUK KELAS V SD - Syari, Elsy Melia; Sumarmin, Ramadhan; Ahda, Yuni (Kolaboratif, 2013)
At alementary schools, textbooks are found to put emphasis only on what should be learned by the students rather than how should the materials be delivered to the students, in these books, students mostly read long explanations and the are rarely supported by picture which are believed to make the materials more understandable. As the result, the students are not able to be engaged in the learning process as they cannot comprehend the materials. This research is aimed to develop the valid, practical and effective and learning materials. This research used CTL to develop the learning materials in the form of 4D models which consisted of four stages that were define, design and disseminate. To define means analyzing the curriculum and the studentsâ€™ needs. To design means designing the learning materials using CTL. To develop means validating the materials. After validating, the materials would be tried out to 30 students at the fifth grade of SDN 05 Kampung Pondok. There was not disseminating stage in this research. From the result of the research, it was proved that the learning materials in CTL were valid. The tryout has shown that the materials were practical to both teacher and the students. Based on the observations, it can be seen that the students were actively involved in the learning process and their grades were also improve significantly. In conclusions, learning materials built in CTL were valid (3,51%), practical (93,43%) and effective (88,58%). Â